Efficient nitrite determination by electrochemical approach in liquid phase with ultrasonically prepared gold-nanoparticle-conjugated conducting polymer nanocomposites - Faisal, M.; Alam, M. M.; Ahmed, Jahir; Asiri, Abdullah M.; Algethami, Jari S.; Altholami, Raed H.; Harraz, Farid A.; Rahman, Mohammed M. (Frontiers in Chemistry, 2024)
An electrochemical nitrite sensor probe is introduced herein using a modified flat glassy carbon electrode (GCE) and SrTiO3 material doped with spherical-shaped gold nanoparticles (Au-NPs) and polypyrrole carbon (PPyC) at a pH of 7.0 in a phosphate buffer solution. The nanocomposites (NCs) containing Au-NPs, PPyC, and SrTiO3 were synthesized by ultrasonication, and their properties were thoroughly characterized through structural, elemental, optical, and morphological analyses with various conventional spectroscopic methods, such as field-emission scanning electron microscopy, energy-dispersive X-ray spectroscopy, high-resolution transmission electron microscopy, powder X-ray diffraction, X-ray photoelectron spectroscopy, and Brunauer–Emmett–Teller method. The peak currents due to nitrite oxidation were characterized in detail and analyzed using conventional cyclic voltammetry (CV) as well as differential pulse voltammetry (DPV) under ambient conditions. The sensor response increased significantly from 0.15 to 1.5 mM of nitrite ions, and the sensor was fabricated by coating a conducting agent (PEDOT:PSS) on the GCE to obtain the Au-NPs/PPyC/SrTiO3 NCs/PEDOT:PSS/GCE probe. The sensor’s sensitivity was determined as 0.5 μA/μM∙cm2 from the ratio of the slope of the linear detection range by considering the active surface area (0.0316 cm2) of the flat GCE. In addition, the limit of detection was determined as 20.00 ± 1.00 µM, which was found to be satisfactory. The sensor’s stability, pH optimization, and reliability were also evaluated in these analyses. Overall, the sensor results were found to be satisfactory. Real environmental samples were then analyzed to evaluate the sensor’s reliability through DPV, and the results showed that the proposed novel electrochemical sensor holds great promise for mitigating water contamination in the real samples with the lab-made Au-NPs/PPyC/SrTiO3 NC. Thus, this study provides valuable insights for improving sensors for broad environmental monitoring applications using the electrochemical approach.